Adolescent Motivations to Engage in Pro‐Social Behaviors and Abstain From Health‐Risk Behaviors: A Self‐Determination Theory Approach. Issue 5 (13th October 2014) - Hardy, Sam A.; Dollahite, David C.; Johnson, Natalie; Christensen, Justin B.
Abstract The present study used self‐determination theory to examine adolescents' motivations to engage in charitable donating and community volunteering and to abstain from sexual intercourse and marijuana use. The sample consisted of 419 late adolescents recruited from across the country through an online survey panel. Participants completed online measures of motivations to engage in donating and volunteering, motivations to abstain from sex and marijuana, and single‐item indexes of the four behaviors. Variable‐centered analyses (correlation and regression) found evidence for a general motivational factor, motivational specificity by behavioral domain (positive and negative behaviors), motivational specificity by particular behavior (charitable donating, volunteering, sexual risk‐taking, and marijuana use), and a stronger relative role for autonomous motivations than controlled motivations. Person‐centered analyses (cluster analysis) found four motivation profiles (low motivation, medium motivation, high motivation, and mixed motivation) for all four behaviors and suggested that level of autonomous motivation was a key factor differentiating the groups on levels of behavior. The findings suggest different levels of motivational specificity and highlight the importance of autonomous motivations in predicting behaviors as compared to controlled motivations. Further, similar patterns were found for motivations to engage and to abstain.